Micropropogation of lady’s lace in relation to a virus inciting mosaic disease
Micropropagation technique used for lady’s lace (Pimpinella monoica Dalz.) exhibited that four test media could induce axillary shoot growth from healthy shoot tip explants. Addition of 2, 4-D and coconut milk in MC medium produced callus. Besides, MS